2016
DOI: 10.1097/md.0000000000005708
|View full text |Cite
|
Sign up to set email alerts
|

A simple and practical score model for predicting the mortality of severe fever with thrombocytopenia syndrome patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 15 publications
1
28
1
Order By: Relevance
“…As reported previously [21], the SFTSI of patients at admission, where SFTSI = 5× neurological symptom level + 4× respiratory symptom level + 3× LG10 viral load -2× LN monocyte% -7, can be used to evaluate the severity of SFTS.…”
Section: Evaluating the Severity Of The Sfts Patientsmentioning
confidence: 99%
“…As reported previously [21], the SFTSI of patients at admission, where SFTSI = 5× neurological symptom level + 4× respiratory symptom level + 3× LG10 viral load -2× LN monocyte% -7, can be used to evaluate the severity of SFTS.…”
Section: Evaluating the Severity Of The Sfts Patientsmentioning
confidence: 99%
“…Another similar phlebovirus , named Heartland virus , was reported as the cause of two cases of severe febrile illness with thrombocytopenia in Missouri, USA [ 6 ]. SFTS is characterized by fever, thrombocytopenia, leukocytopenia, elevated alanine and aspartate amino transferases, proteinuria and various other systemic manifestations including muscular symptoms, respiratory symptoms, gastrointestinal symptoms, neurological disorders and coagulopathy [ 7 , 8 ]. It has become a significant public health threat with an estimated high case-fatality rate of 12.7% to 32.6% [ 5 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had reported many risk factors associated with fatal outcomes [ 5 , 7 , 8 , 11 , 16 , 17 ]. For example, senior people is more likely to have a fatal clinical outcome [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations